2018
DOI: 10.1177/1470785317744667
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous consumption and the rising importance of experiential purchases

Abstract: More than 100 years ago, the term conspicuous consumption was coined. In the economist tradition, emphasis was always on the demonstration of wealth, income, and status by material purchases. However, conspicuous consumption not only means the ostentation of wealth but also the demonstration of something symbolic that is more immaterial. There is an increasing importance of immaterial experiences over material things in the current cultural climate. This study investigates the role of conspicuous consumption f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 36 publications
1
51
0
4
Order By: Relevance
“…These results contribute to a large body of literature that suggests individuals engage in ecotourism, at least in part, due to their internalized values regarding the environment ( Brown, 2012; Perkins & Grace, 2009;Weaver & Lawton, 2002). However, social return was found to have additional explanatory power as a predictor of ecotourism intention, thus adding to a growing body of research that suggests social media and self-promotion are becoming salient factors regarding tourism behavior (Boley et al, 2018;Bronner & de Hoog, 2018;Dinhopl & Gretzel, 2016;Lo & McKercher, 2015;Lyu, 2016;Munar & Jacobsen, 2014;Taylor, 2020).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…These results contribute to a large body of literature that suggests individuals engage in ecotourism, at least in part, due to their internalized values regarding the environment ( Brown, 2012; Perkins & Grace, 2009;Weaver & Lawton, 2002). However, social return was found to have additional explanatory power as a predictor of ecotourism intention, thus adding to a growing body of research that suggests social media and self-promotion are becoming salient factors regarding tourism behavior (Boley et al, 2018;Bronner & de Hoog, 2018;Dinhopl & Gretzel, 2016;Lo & McKercher, 2015;Lyu, 2016;Munar & Jacobsen, 2014;Taylor, 2020).…”
Section: Discussionsupporting
confidence: 51%
“…Beginning in the late 19 th century and continuing with the rise of photography, taking photographs within destinations has become an important part of tourism experiences for travelers (Snow, 2008). While the distribution of travel photographs was once limited to a small network of family and friends, social media is expanding this network and transforming the ways in which travel photographs are used by tourists to portray themselves and their travel experiences (Boley et al, 2018;Bronner & de Hoog, 2018;Dinhopl & Gretzel, 2016;Lo & McKercher, 2015;Lyu, 2016;Munar & Jacobsen, 2014;Taylor, 2020).…”
Section: Social Media and Tourismmentioning
confidence: 99%
“…For example, just as people think of their experiential purchases as more significant elements of who they truly are than their material purchases, they likewise believe they learn more about another person's “true self” from that person's experiential purchases than his or her material purchases (Carter & Gilovich, , Studies 3a–3c). And just as people with an especially strong need to understand or get in touch with their true self are especially motivated to seek out experiential purchases (Hornik & Diesendruck, ; Kim, Seto, Christy, & Hicks, ), people who want to signal their true self to others are likewise especially inclined to make experiential purchases—and to advertise that they have made them (Bronner & de Hoog, ).…”
Section: Sources Of the Experiential Advantagementioning
confidence: 99%
“…In a study into the relationship between an experiential product (holiday choice) and conspicuous consumption (see Bronner & de Hoog, 2018), it was found that displaying status as well as identity by means of your holiday does play a role in choosing a vacation. A large majority of people are convinced that, in general, the choice of a summer holiday says a lot about what kind of person someone is.…”
mentioning
confidence: 99%